The Unequal Distribution of Linguistic Capital in a Transnational Economic Order - Rössel, Jörg; Schroedter, Julia H. (Frontiers in Sociology, 2021)
Foreign language proficiency is an unequally distributed form of linguistic capital that is becoming increasingly important in contemporary societies: first, it enables persons to participate transnationally in educational activities and in labor markets beyond the national institutions of their home country. It is also crucial for integrating an increasing share of the population with a migration background into the labor market. Thus, this article focuses on the explanation of language proficiency. Its main aim is to enrich the discussion in this field by deriving hypotheses from the sociological theory of reproduction and the discourse on migrant integration. Variables are included which have not been tested in a broad fashion in previous empirical research. We use data on different groups of migrants and non-migrants in multilingual Switzerland, where we could study the determinants of the unequal distribution of language proficiency in three official languages and foreign language repertoire in general. Our main results show that the hypotheses derived from the two theoretical discussions are empirically supported overall and contribute substantially to the explanation of language proficiency. However, most of these variables indicate the importance of unequally distributed opportunities for learning languages, thus highlighting that language learning may be part of the general process of reproducing social inequality structures.